PTU-033 Serum metabolite profiles differentiate Crohn's disease from ulcerative colitis and from healthy controls. (23rd September 2015) - Johnston, C; Dunn, W; Broadhurst, D; Brown, M; Makin, A; Campbell, S; Goodacre, R; Newman, W; Watson, A J M
Abstract : Introduction: Metabolomics is a powerful scientific strategy which identifies low molecular weight (bio)chemicals (metabolites) present in the metabolome of a cell, tissue or organism. The aim of this study was to undertake a two-stage metabolomic study of circulatory serum from patients with ulcerative colitis (UC) and Crohn's disease (CD) and matched healthy controls, to determine if we could establish a characteristic metabolic signature for each of these diseases. Methods: Patients were selected from a cohort of 332 IBD patients, comprising 134 males and 198 females during November 2007–March 2009. The base study comprised 30 CD, 30 UC and 29 control patients, all white male <65 years old and of Caucasian ethnicity. The validation study comprised 31 CD, 28 UC and 29 matched control patients. In the validation study, multiple matched ethnicities were recruited. Serum was analysed by Ultra Performance Liquid Chromatography-Mass Spectrometry and subject to univariate analysis using Mann–Whitney or Student t test. Results: After quality assurance, 4289 peaks were consistently detected by the UPLC-MS analysis of the base study samples. After univariate screening (p<0.05) this was reduced to 909 information rich peaks which discriminated in pair-wise comparisons. Of these, 769 were also detected in the validation study (85%). For both data sets, there is good discrimination between each of the disease populations and the control populations. The degree of separation is similar for both diseases. The discrimination between UC and CD is less distinct;however there is a significant difference in the metabolic profiles, and therefore the phenotypes of the diseases. For each peak, in the base and validation data sets, three separate univariate comparisons were performed: CD vs. Control, UC vs. Control and, UC vs. CD. For CD vs. Control, 255 features had a p-value < 0.05 in both the base and validation tests, compared with 138 significant features for UC vs control, and 35 significant features for UC vs. CD. Of these 117, 58 and 17, respectively were chemically identified and provided 61, 30 and 9 unique metabolite identification(s). Conclusion: This study illustrates, for the first time, that serum metabolomics is effective at distinguishing IBD patients from normal subjects, and to a lesser extent CD from UC. It demonstrates the potential of metabolomics to differentiate disease phenotypes and may give new insights into the aetiology of IBD.